DIGITAL SELF-DETERMINATION IN THE CONTEXT OF ECONOMY DIGITALIZATION - Skosyreva, Nina; Kolesnik, Mikhail (Revista Inclusiones, 2020)
This article discusses the problem of digital self-determination of personality under conditions of economy digitalization. The main attention is focused on the fact that a modern person is a changing person in changing world, who should rapidly and continuously adapt to a new reality, impregnated with digital communications and relations. Under such conditions, it is possible to raise the issue about transformation of human capital into digital capital. This article analyzes the concept of digital capital used for substantiation of necessity of new consideration of personality, which assumes market-related and intellectual approach, where personality and profession become both a brand, a product and an instrument, which allows talking about close connection between personal and professional self-determination. Given the various aspects of the process of personal self-determination, the authors substantiate possibility to introduce the concept of digital selfdetermination into scientific usage. It should be mentioned that a modern human, being simultaneously a subject and an object of digital economy, is not always ready to reach the full depth of his personal and professional self-determination due to the level of his personal growth, either due to those social economic and political legal conditions provided by the social reality, where the human executes self-determination.